The effect of corticosteroids on quality of life in a sarcoidosis clinic: The results of a propensity analysis. Issue 4 (April 2015) - Judson, Marc A.; Chaudhry, Haroon; Louis, Amanda; Lee, Kevin; Yucel, Recai
Summary: Background: Both sarcoidosis and its treatment may worsen health related quality of life (HRQoL). We performed a propensity analysis of sarcoidosis-specific HRQoL patient reported outcome measures (PRO) to disentangle the effects of sarcoidosis and corticosteroid therapy on HRQoL in sarcoidosis outpatients. Methods: Consecutive outpatient sarcoidosis patients were administered modules from two sarcoidosis-specific HRQoL PROs: the Sarcoidosis Health Questionnaire (SHQ) and the Sarcoidosis Assessment Tool (SAT). Patients were divided into those that received ≤500 mg of prednisone (PRED-LOW) versus >500 mg of prednisone (PRED-HIGH) over the previous year. SAT and SHQ scores were initially compared in the two corticosteroid groups. Then a multivariate analysis was performed using a propensity score analysis adjusted for race, age, gender and the severity of illness. Results: In the unadjusted analysis, the PRED-HIGH group demonstrated the following worse HRQoL scores compared to the LOW-PRED group: SHQ Daily (p = 0.02), SAT satisfaction (p = 0.03), SAT daily activities (p = 0.03). In the propensity analysis, the following domains demonstrated worse HRQoL in the PRED-HIGH group than the PRED-LOW group: SAT fatigue (p < 0.0001), SAT daily activities (p = 0.03), SAT satisfaction (p = 0.03). All these differences exceeded the established minimum important difference for these SAT domains. The SHQ Physical score appeared to demonstrate a borderline improved HRQoL in the PRED-HIGH versus the PRED-LOW group (p = 0.05).). In a post-hoc exploratory analysis, the presence of cardiac sarcoidosis may have explained the quality of life differences between the two corticosteroid groups. Conclusions: Our cohort of sarcoidosis clinic patients who received ≤500 mg of prednisone in the previous year had an improved HRQoL compared to patients receiving >500 mg on the basis of two sarcoidosis-specific PROs after adjusting for severity of illness. These data support the need to measure HRQoL in sarcoidosis trials, and suggest that the search should continue for effective alternative medications to corticosteroids.